2005
DOI: 10.1002/maco.200403803
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of magnesium alloys in commercial engine coolants

Abstract: A number of magnesium alloys show promise as engine block materials. However, a critical issue for the automotive industry is corrosion of the engine block by the coolant and this could limit the use of magnesium engine blocks. This work assesses the corrosion performance of conventional magnesium alloy AZ91D and a recently developed engine block magnesium alloy AM-SC1 in several commercial coolants. Immersion testing, hydrogen evolution measurement, galvanic current monitoring and the standard ASTM D1384 test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(27 citation statements)
references
References 11 publications
0
22
0
5
Order By: Relevance
“…It is clearly shown that AM-SC1 was more severely corroded by the MBL coolant than in the LLC-T coolant (Long life coolant (Red), Genuine Toyota part, a modern organic acid-based long life coolant) +1 wt% KF while the other materials were still intact in both coolants. [134] These results suggest the acceptability of LLC-T+1 wt% KF for use in an AM-SC1 engine block.…”
Section: Coolant Corrosion and Inhibitionmentioning
confidence: 70%
See 4 more Smart Citations
“…It is clearly shown that AM-SC1 was more severely corroded by the MBL coolant than in the LLC-T coolant (Long life coolant (Red), Genuine Toyota part, a modern organic acid-based long life coolant) +1 wt% KF while the other materials were still intact in both coolants. [134] These results suggest the acceptability of LLC-T+1 wt% KF for use in an AM-SC1 engine block.…”
Section: Coolant Corrosion and Inhibitionmentioning
confidence: 70%
“…For example, Mobil coolant 33 plus (MBL) is a traditional inorganic coolant. It is more corrosive to AM-SC1 at room temperature than at the high temperature of 95 C. [134] The average general corrosion rate of AM-SC1 (a new alloy with rare earth elements, zinc and zirconium as the main alloying elements, which was developed as an engine block material [119,120] ) immersed in MBL decreases as temperature increased. When the temperature was lower than 85 C, the general corrosion rate became unacceptable.…”
Section: Coolant Corrosion and Inhibitionmentioning
confidence: 99%
See 3 more Smart Citations